Transmission of Harmonic Signals Through a Wire Media (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2018)
This paper is devoted to wire media (WM) investigation for signal transfer devices. Such devices are promising for diﬀerent applications as imaging, power or signal transfer, sensing etc. However, first WMs could be used as a resonance structures, because the transfer of electromagnetic (EM) waves was possible only at the Fabry-Perot frequencies. It restricts the number of applications. However, the last works has shown the possibility of the broadband power transfer of evanescent electromagnetic waves. It allows using the same source of EM waves and their receiver to transfer the signals with diﬀerent values of operation frequencies. Another investigation has proved that the WM does not distort the propagation wave. It allowed to suppose the possibility of pixel signal transfer that was studied in the paper and shown the ability of application of the such structures as the multichannel communication systems. With this aim the signals sources were allocated at the same plane with the input WM interface. First of all, the simulation investigations of the electric feld distributions of transferred harmonic signals through the WM have shown the needed period of dipoles allocations for the satisfactory resolution of received harmonic signals. One more conclusion from obtained results is the approvement that in this case the WM is not the resonance structure, but the same one operates with the signals of diﬀerent frequencies. More detailed results and understanding of this were obtained from the spectrum analysis of the signals received at the output interface. It shown that the period of sources 2a is acceptable along x, y and diagonal directions. The spectrum analysis of the shape of the propagation wave also demonstrated and proven that the propagating signals do not suﬀer any nonlinear distortions. In the case of using of WM slab it can provide the excellent coupling between the interaction ports.